(3JaSjQ cJGH GdQMeI dLGHQ Hf MjGfs - (3eLghds; (3CHh ehSi,J (B200 (3g` s
(3ChdgG (B:s
(3gPG GNJUGQ (B"(3GdQMeI(B" (3deG aQZ ef OjHGLJg bGd(B: (3JOHQ CjgG GdYGbd ai cJHge s
(3BNQgG (B:s
(3hdGYfGA ajg HYO agec gPG GdcJGH Je HYhf Gddg GYde Cfge GJabhG HeKd cJGH GdQMeI dLGHQ Hf MjGf QMeg Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B192 - (3U(B196s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs